Outcomes among patients with Staphylococcus aureus bacteremia enrolled in a postdischarge outpatient parenteral antibiotic therapy program at an academic medical center - Deborah A. Theodore; E. Yoko Furuya; Eloise Austin; William G. Greendyke (Cambridge University Press, 2022)
We compared patients with Staphylococcus aureus bacteremia enrolled in outpatient parenteral antibiotic therapy monitoring program (OPAT-MP) upon hospital discharge with patients not enrolled. OPAT-MP patients were more likely to attend infectious diseases follow-up appointments. OPAT-related emergency room visits and/or readmissions were more common among non-OPAT-MP patients, but differences were not statistically significant.